Desain Sistem Informasi Perpustakaan Universitas Antakusuma Menggunakan Platform SLiMS (Senayan Library Management System) - Hanindito, Gregorius (Jurnal Nasional Teknologi Komputer, 2023)
Library is one of the important elements in higher education institutions because library provides various forms of references and literature for lecturers and students according to their needs and scientific fields. The same thing happened at Antakusuma University which is one of the higher education institutions located in Pangkalan Bun, Central Kalimantan. At Antakusuma University, the library management is divided into 1 (one) Central Library Unit which is managed at the university level and 4 (four) faculty library sub-units which include: 1) Faculty of Economics Library; 2) Law Faculty Library; 3) Library of the Faculty of Agriculture; and 4) Engineering Faculty Library. However, the existence of the library units at Antakusuma University are not managed properly, because all activities are carried out manually so that they are considered less effective and efficient. In addition, there is no interconnection between the central library and the faculty library units which makes the management of the library units and sub-units is still independent. Based on the background mentioned above, this research aims to design and build a library information system using the open source Senayan Library Management System (SliMS) platform which can facilitate the computerized library management process which is more effective and efficient than before. In addition, this research also aims to integrate the central library and the faculty library which were previously managed independently. The output of this study is in the form of a library information system application that can be used by the Antakusuma University library unit.